The Small Ones Matter—sHsps in the Bacterial Chaperone Network - Obuchowski, Igor; Karaś, Piotr; Liberek, Krzysztof (Frontiers in Molecular Biosciences, 2021)
Small heat shock proteins (sHsps) are an evolutionarily conserved class of ATP-independent chaperones that form the first line of defence during proteotoxic stress. sHsps are defined not only by their relatively low molecular weight, but also by the presence of a conserved α-crystallin domain, which is flanked by less conserved, mostly unstructured, N- and C-terminal domains. sHsps form oligomers of different sizes which deoligomerize upon stress conditions into smaller active forms. Activated sHsps bind to aggregation-prone protein substrates to form assemblies that keep substrates from irreversible aggregation. Formation of these assemblies facilitates subsequent Hsp70 and Hsp100 chaperone-dependent disaggregation and substrate refolding into native species. This mini review discusses what is known about the role and place of bacterial sHsps in the chaperone network.